BULEKANG: CULTIVATION OF CATFISH KANGKUNG TO ACHIEVE ZERO HUNGER AND INCREASE COMMUNITY INCOME IN PASIRHARJO VILLAGE BLITAR REGENCY - Nurina Hasanatuludhhiyah; Alissa Qodrunnada (Universitas Airlangga, 2022)
Food security is one of the efforts to realize the 2nd sustainable development goal, namely zero hunger. In order to help the government encourage the realization of food security in Indonesia, the community service team of Universitas Airlangga implemented a bulekang (kale catfish cultivation) program aimed at the people of Pasirharjo village, Talun subdistrict, Blitar regency. The purpose of the bulekang program is to increase knowledge about food security, the use of home land as a container for the fulfillment of animal nutrition, vegetable and entrepreneurial containers, and help the government increase community income. The methods used in this activity are extension and training (field practice). The average pretest result regarding catfish cultivation was 35.5 and posttest 97 while the average pretest regarding kale cultivation was 36 and the average posttest was 98. This indicates that the training material can be understood by participants. Based on the evaluation of attitudes and behaviors, it was obtained that the participants of the activity had a high willingness to practice bulekang in their respective homes. This training is very useful to increase the creativity and income of citizens in pandemic times. Keywords: food security, bulekang, zero hunger, income DAFTAR PUSTAKA Adharani, Nadya. 2021. “Pengabdian Kepada Masyarakat Melalui Budikdamber Upaya Pemenuhan Gizi Ikan Dimasa Pandemi Covid-19 Di Kelurahan Taman Baru Kecamatan Banyuwangi.” Jurnal Ilmu Perikanan dan Kelautan 3, no. 1: 1–7. https://doi.org/10.36526/lemuru.v3i1.1272. Astawan, M. 2008. “Lele Bantu Pertumbuhan Janin.” 2008. http://wilystra2007.multiply.com/%0Ajournal/item/62/Lele_Bantu_Pert%0Aumbuhan_Janin. Badan Ketahanan Pangan. 2019. “Indeks Ketahanan Pangan Indonesia 2019 (Food Security Index of Indonesia 2019).” Food Security Bureau, Republic of Indonesia, 14. http://bkp.pertanian.go.id/storage/app/media/Bahan 2020/IKP 2019 FINAL.pdf. Bappenas. 2021. “Study of Food Loss and Waste in Indonesia.” Hadiputri, T. 2021. “Pengenalan Budikdamber (Budidaya Ikan dalam Ember) untuk Ketahanan Pangan di Kecamatan Dringu Kabupaten Probolinggo” 2, no. 1: 42–45. Hidayati, Nurul, Pienyani Rosawanti, Fitriadi Yusuf, dan Nanang Hanafi. 2017. “Kajian Penggunaan Nutrisi Anorganik terhadap Pertumbuhan Kangkung (Ipomoea reptans Poir) Hidroponik Sistem Wick.” Daun: Jurnal Ilmiah Pertanian dan Kehutanan 4, no. 2: 75–81. https://doi.org/10.33084/daun.v4i2.81. Kesehatan, Kementerian. 2018. “Riset Kesehatan Dasar (Riskesdas).” Lasminingrat, L. dan Efriza. 2020. “Pembangunan Lumbung Pangan Nasional: Strategi Antisipasi Krisis Pangan Indonesia.” Jurnal Pertahanan & Bela Negara 10, no. 3: 243. https://doi.org/10.33172/jpbh.v10i3.1053. Manuhara, Y., Utami, E.S & Yachya, A. 2018. “Pelatihan Budidaya Sayuran Organik secara Aquaponik melalui Kegiatan Iptek bagi Masyarakat pada Peternak Lele di Desa Lebo Kabupaten Sidoarjo.” Jurnal Layanan Masyarakat Universitas Airlangga 2, no. 1: 12–17. Mardikanto, T. 1993. “Penyuluhan Pembangunan Pertanian.” In Sebelas Maret University Press. Surakarta. Pandiangan, Maruba, Jamaran Kaban, Basuki Wirjosentono, dan Jansen Silalahi. 2020. “Analisis Asam Lemak Omega 3 dan 6 pada Minyak Ikan Lele secara GC-FID.” Jurnal Riset Teknologi Pangan Dan Hasil Pertanian (RETIPA) 1: 22–29. https://doi.org/10.54367/retipa.v1i1.908. Radimer, K. 2002. “Measurement of household food security in the USA and other industrialised countries.” Public Health Nutrition 5, no. 6a: 859–64. https://doi.org/10.1079/phn2002385. Rahayu, D., A. Piranti, dan I. Sihwaningrum. 2019. “Diversivikasi Hasil Olahan Ikan Lele Di Desa Kaliwangi Kecamatan Purwojati Kabupaten Banyumas.” Dinamika Journal : Pengabdian Masyarakat 1, no. 1: 54–61. https://doi.org/10.20884/1.dj.2019.1.1.602. Sofiari, E. 2009. “Karakterisasi Kangkung Varietas Sutera berdasarkan Panduan Pengujian Individual.” Buletin Plasma Nutfah 15, no. 2: 4950. Supendi, M. dan Fajar, S. 2015. “Teknik Budidaya Yumina Sistem Aliran Atas di Bak Terpal.” Buletin Teknik Literatur Akuakultur 13, no. 1: 101–6. Suratha, I. 2015. “Krisis Petani Berdampak pada Ketahanan Pangan di Indonesia.” Media Komunikasi Geografi 16, no. 1: 67–80. Suryana, Achmad. 2014. “Menuju Ketahanan Pangan Indonesia Berkelanjutan 2025: Tantangan dan Penanganannya.” Forum penelitian Agro Ekonomi 32, no. 2: 123–35. https://doi.org/10.21082/fae.v32n2.2014.123-135. Susetya, I., dan Z. Harahap. 2018. “Aplikasi Budikdamer (Budidaya Ikan lele dalam Ember) untuk Keterbatasan Lahan Budidaya di Kota Medan.” Abdimas Talenta 3, no. 2: 416–20. Swardana, Ardli. 2020. “Optimalisasi Lahan Pekarangan Sebagai Salah Satu Upaya Pencegahan Krisis Pangan di Masa Pandemi Covid-19.” Jagros : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science) 4, no. 2: 246. https://doi.org/10.52434/jagros.v4i2.922. Talun, PNPM MPD Kecamatan. 2011. “Profil Desa Pasirharjo.” 2011. http://pnpmmpd-talun.blogspot.com/2011/11/profil-desa-pasirharjo.html. Ubaidillah, A., dan W. Hersoelistyorini. 2010. “Kadar Protein Dan Sifat Organoleptik Nugget Rajungan Dengan Substitusi Ikan Lele (Clarias Gariepinus).” Jurnal Pangan dan Gizi 1, no. 2: 116029. https://doi.org/10.26714/jpg.1.2.2010. Unit, The Economist Intelligence. 2021. “Global Food Security Index.” Zaki. 2009. “Budi Daya Ikan Lele (Clarias batrachus).”